On-line adaptive and real-time intrafraction motion management of spine-SBRT on an MR-linac - Cunningham, Justine M.; Chin Snyder, Karen; Kim, Joshua P.; Siddiqui, Salim M.; Parikh, Parag; Chetty, Indrin J.; Dolan, Jennifer L. (Frontiers in Physics, 2022)
Purpose: The superior soft-tissue contrast of MRI-guided radiotherapy offers enhanced localization accuracy of the spinal cord in spine Stereotactic Body Radiotherapy (SBRT). This work includes a planning study for spine-SBRT on an MR-Linac. Additionally, a patient with spine metastasis was treated using an adaptive radiation therapy (ART) workflow. We report our initial experience of targeting accuracy, image-guided localization, on-line adaptive planning, and treatment with real-time intrafraction imaging with automatic beam gating. Methods: Six spine-SBRT patients were retrospectively re-planned to 18 Gy in 1-fraction on a commercial, Monte Carlo-based MR-Linac treatment planning system. Plans were generated using 9-13 step-and-shoot intensity-modulated radiation therapy 6MV-flattening filter free beams and optimized to achieve plan quality criteria recommended by RTOG-0631. One thoracic vertebral body clinical case was treated to 27 Gy in 3-fractions utilizing ART, where daily anatomical changes were accounted for via re-planning and treatment in an on-line manner to account for limited ability to correct rotational setup uncertainties. Results: Plans met all critical-tissue constraints outlined in RTOG-0631 and AAPM Task Group-101, while covering 90% of the target with the prescription dose. Clinically, visibility of the spinal cord allowed for patient setup focusing on spinal cord-alignment. Utilization of the online ART workflow, while re-contouring the target and spinal cord, enabled an increase in prescription dose coverage from 89% to 95% in two of three fractions while maintaining acceptable doses to organs-at-risk. Real-time MR-cine imaging demonstrated sufficient quality for the automatic beam gating algorithm to provide intrafraction motion management of the spinal canal utilizing a 3.0 mm gating boundary and 1-2% region of excursion allowance, in the sagittal plane. A decrease in coverage, below the 95% threshold was noted in post-treatment volumetric imaging due to lateral movement not observed during real-time gating. Conclusion: Achieved plan quality and deliverability was within accepted standards. MR-guidance with an on-line ART workflow offered increased accuracy in the localization of the spinal cord at the time of treatment to enhance both tissue sparing and target volume coverage. Increased spatial resolution of cine-images, and tracking in three-dimensions would be beneficial for future spine-SBRT treatments on the MR-Linac.